Masa Depan Hak Atas Air Pasca Putusan Mahkamah Konstitusi No. 85/PUU-XI/2013 - Yordan Gunawan (Universitas Janabadra, 2016)
The right to water is a fundamental part of our human rights and of people understanding of a life in dignity. The right to water implies the right to drinking water and to adequate sanitation. The Constitutional Court (MK) on 18 February 2015, by Decision No. 85/PUU-X/2013 nullified the Law No. 7 of 2004 on Water Resources. The article aims to discuss about the future of water rights in Indonesia after the decision of the Constitutional Court No. 85/PUU-X/2013. The study is normative legal research with Statute Approach. Using the qualitative descriptive method, the study describe right of water as one of the human rights which explicitly stated in Indonesian Constitution, especially Article 28 (H), Article 33, and also many other instruments of human rights. Furthermore, the article also explore that constitutionally, the responsibility of state is enacting the pros and fair policies that support and enhance the quality for the people to access the water itself. States also have to fulfill and protect those rights from privatization, which will reduce the right of the people. The result shows that after the Decision of Indonesian Constitutional Court No. 85/PUU-XI/2013, that nulling the Law No. 7 Year 2004 on Water Resource and reenacted the Law No. 11 Year 1974 on Irrigation is the most proper way to return backs the access for public to access water which for a long time was occupied by private sector. However, the Irrigation Law Year 1974 did not provide the regulation on how to respect, to fulfill and to protect the right and access to water and it will be homework for the Government to realize it.Keywords: Human Rights, Right to Water, Constitutional Court Decision, Privatization